THE EFFECT OF SOCIAL MEDIA ADVERTISING AND SOCIO-ECONOMIC STATUS ON LUXURY BRAND PURCHASE INTENTION MODERATED BY THE LIFESTYLE OF GENERATION Z CONSUMERS IN MAKASSAR CITY - Nurfajriyanti, Adelia (Study of Scientific and Behavioral Management, 2024)
The development of luxury brand sales in Indonesia continues to increase every year along with the increasing economy of the upper middle class. The tendency of Indonesian consumers to buy luxury goods is 44%. Consumers have different motives in buying luxury brand products, either for the experience or even to show their status around them. This study aims to determine the Influence of Social Media Advertising and Socioeconomic Status on Luxury Brand Purchase Intentions Moderated by the Lifestyle of Generation Z Consumers in Makassar City.This research is an associative study using a quantitative approach. This study uses primary data and secondary data, the sampling technique in this study is using a non-probability sampling technique (non-probability sampling) using the Hair formula, so that the number of samples in this study is 112 respondents. Data analysis in this study uses Structural Equation Modeling (SEM) using the help of smartPLS version 4.0 for windows. Based on the results of this study, it shows that the social media advertising variable has a positive and significant effect on purchase intention, the socioeconomic status variable has a positive and significant effect on purchase intention, lifestyle does not moderate the effect of social media advertising on purchase intention, lifestyle moderates the effect of socioeconomic status on purchase intention.